Dramatically improving thermoplasticity of FGH4096 superalloy by a novel sub-solvus temperature holding followed by extremely slow cooling - Zhiling Liu; Wei Liu; Hua Zhang; Jingjing Ruan; Hailiang Huang; Xin Zhou; Fanchao Meng; Shangzhou Zhang; Liang Jiang (Journal of Materials Research and Technology, 2023)
In this work, the thermoplasticity of hot extruded (HEXed) FGH4096 superalloy was greatly enhanced by sub-solvus temperature holding followed by extremely slow cooling (S-ESC). After S-ESC processing, the dispersed fine γ′ precipitates inside the grains and grain boundaries obviously grow up. Under most deformation conditions, the S-ESCed samples exhibit smaller flow stress and larger strain rate sensitive index (m) values than the HEXed samples, especially the peak value of m is 0.75 vs. 0.32. This is because fine γ′ precipitates limit deformation by pinning dislocation, and coarse γ′ precipitates promote dynamic recrystallization (DRX). Under the high strain rate of 1 s−1, the DRX degree of the HEXed sample is greatly affected by temperature, while the S-ESCed samples maintain a high DRX degree at different temperature. At the high temperature of 1100 °C, the S-ESCed samples exhibit smaller grain sizes and higher DRX degrees than the HEXed sample under low strain rates. More importantly, because the γ′ precipitates promote DRX, the S-ESCed sample achieves superplasticity at 1090 °C and 10−3 s−1.